(untitled) (Journal of Finance, Business and Management Studies, 2022)
In today’s global markets, categorized by enormously fast modifications in technology and customer’s demand, and by product life cycle getting shorter and shorter, a single firm has not the ability to be competitive if it is not included in a network that, operating as a single entity, is able to react to demand energy and unpredictability. Therefore, existing supply chains, designed in a global sourcing view, are highly vulnerable to worries resulting from a strong dependence on other network’s players, such as suppliers or logistics providers. In this difficult and competitive context, properly measuring and managing risks connected to the different stages of the value chain, as well as external and not directly controllable risks, means being able to ensure connection in supply. This paper attention on the particular field of the retail industry since its highly unpredictable demand and particularly short life cycle make it very important to examine risks connected to the supply chain. In fact, more suitable for real composite problems that cannot be completely denoted through a simple classified structure. The achieved results show that supply chain efficiency, in terms of correct management of both material and informative flows, is considered the most important part also for a demand-driven supply chain as the retail industry one which, in adding, is constantly looking for customer tastes and always changing trends.